2020
DOI: 10.1111/add.14896
|View full text |Cite
|
Sign up to set email alerts
|

Comparing rates and characteristics of ambulance attendances related to extramedical use of pharmaceutical opioids in Victoria, Australia from 2013 to 2018

Abstract: Background and aims Despite increases in opioid prescribing and related morbidity and mortality, few studies have comprehensively documented harms across opioid types. We examined a population-wide indicator of extramedical pharmaceutical opioid-related harm to determine if the supply-adjusted rates of ambulance presentations, the severity of presentations or other attendance characteristics differed by opioid type. Design Retrospective observational study of coded ambulance patient care records related to ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…5 Similar research using Australian ambulance attendance data found that different pharmaceutical opioids have distinct patterns of harm. 6 For example, the highest rates of opioid-related ambulance attendance were accounted for by the lowest potency opioid, different opioids were associated with accidental overdoses versus suicidal Strengths and limitations of this study ► Indicator of population-level opioid harm. ► Cases have been selected using International Classification of Diseases 10th Revision (ICD) codes and free-text searches, increasing the capture of relevant cases over studies that use ICD codes alone.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…5 Similar research using Australian ambulance attendance data found that different pharmaceutical opioids have distinct patterns of harm. 6 For example, the highest rates of opioid-related ambulance attendance were accounted for by the lowest potency opioid, different opioids were associated with accidental overdoses versus suicidal Strengths and limitations of this study ► Indicator of population-level opioid harm. ► Cases have been selected using International Classification of Diseases 10th Revision (ICD) codes and free-text searches, increasing the capture of relevant cases over studies that use ICD codes alone.…”
Section: Introductionmentioning
confidence: 94%
“…13 Victoria's per capita rate for unintentional pharmaceutical-opioid induced deaths is comparable with other Australian jurisdictions, 14 and previous work demonstrated that Victorian rates of ambulance attendance for extramedical pharmaceutical opioid use were broadly consistent with other jurisdictions. 6 Australia has the eighth highest per capita licit pharmaceutical opioid consumption in the world. 2 This population-wide study has a catchment area of the entire Victorian state, for the past 10 years (July 2009-June 2019), for individuals aged 12 years of age and older.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations